Observer-Based Event-Triggered Fuzzy Integral Sliding Mode Control for Hindmarsh Rose Neuronal Model Via T-S Fuzzy systems - Nirvin, P.; Rakkiyappan, R. (Journal of Applied Nonlinear Dynamics, 2026)
The problem of stability for nonlinear Hindmarsh-Rose (H-R) neuron model with event-triggered fuzzy Integral Sliding Mode Control (ISMC) design is investigated via Takagi-Sugeno (T-S) fuzzy systems. The Event-triggered Communication (ETC) scheme is introduced with a triggered condition of the sampling instant to determine whether the current sampled signal should be transmitted or not. In order to send and receive the delay measurements for updating the control, the event triggered zero-order-holder (ZOH) is employed. Also, a note observer is designed for the estimation of system state and for the facilitation of the sliding surface design. Then by analyzing the measured output and observer output, a novel law is presented. Further the stability criterion and the stabilization conditions are estimated based on Lyapunov-Krasovskii functional (LKF) to ensure the asymptotically stability for the considered system. Finally, a numerical example is presented to demonstrate the feasibility of the proposed design scheme.